TEACHING STUDENTS READING COMPREHENSION SKILL OF DESCRIPTIVE TEXT THROUGH RPG - Farhan, Elha Ramadhoni; Susilawati, Endang; Rezeki, Yanti Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this research was to find out whether or not the use of RPG effective in teaching reading comprehension of descriptive text to the eighth grade students of SMPN 2 Pontianak in academic year 2018/2019. This research was a pre-experimental research design by using one group pre-test and post-test. The population of the research is the eighth grade students’ of SMPN 2 Pontianak which consists of 249 students. From the populations, class VIII H has been chosen as sample with 30 students and the data were collected by measurement technique. Referring to the research findings, it showed that the RPG was effective to enhance students’ reading comprehension due to the increasing of the students’ reading achievement. It was proved by calculating the t-test calculation result (7.47) which was higher than the t-critical (2.045) and the effect size was 1,17 categorized as strong effect. It means that the use of RPG for teaching reading comprehension had increased the students’ skill in reading comprehension of descriptive text. There was significance different result between the pre-test and post-test. The students’ reading score increased and students could understand the text well and enjoyed in learning English. Keywords:Descriptive text, Reading comprehension,Role-playing game